Pengaruh Rasio Tekanan Kompresor Turbocharger Terhadap Kinerja Mesin Diesel dan Emisi NOX - Matheus Dwinanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
The use of a turbocharger in large diesel engines has become a demand because it can increase engine output and efficiency by utilizing exhaust gas from combustion (exhaust gas). Turbocharger is a device to increase the intake of air into the cylinder by utilizing the energy of exhaust gases from combustion. The purpose of this study is to analyze the effect of differences in the turbocharger pressure ratio on diesel engine performance using Diesel-RK software. The diesel engine under study is model 4D56 2.5L which uses a single turbocharger with maximum power of 136 PS at 4000 rpm and maximum torque of 324 N.m at 2000 rpm. The compressor pressure ratio under study was only 1.5 and 2.5 compared to a diesel engine without a turbocharger or natural aspirated engine (NA). The engine capacity is 2477 cc, 4 cylinders, and the compression ratio is 18:1. The fuel used is SME Biodiesel (Soya Methyl Ester, C15H28) with a cetane number of 56.5. The results of this study indicate that the use of a turbocharger will lead to an increase in engine power, especially at a high compressor pressure ratio due to the larger air filling when compared to the NA diesel engine for the engine speed range of 750 rpm to 5000 rpm. For diesel engines that use a turbocharger, the BSFC will decrease with increasing engine speed. NOx emissions increase with increasing turbocharger compressor pressure ratio when compared to NA diesel engines, and this occurs over the entire engine speed range (750 rpm – 5000 rpm). NOX emissions decrease as engine speed increases